Supply Chain Flexibility Configurations: Perspectives, Empirical Studies and Research Directions - Arvind Jayant; Harkaran Singh Ghagra (International Journal of Supply Chain Management, 2013)
This paper investigates the current developments in research and practice in the field of supply chain flexibility through content analysis of the published literature. We had scrutinized a wide range of research publications from national and international journals and conferences of high repute. As diversity and uncertainty in the environment increases the companies are responding by adding flexibility as a dimension to their operational strategies. The review examined various perceptions, notions and definitions of flexibility, drivers and sources found in manufacturing and supply chain literature and compared the stated objectives, articulated needs and fundamental beliefs underlying the concepts, from a flexibility decision-performance-synchronization perspective. The objective of this study is to encourage and provide researchers and academicians globally with future research directions in the field of supply chain flexibility and its impact on business performance.Keywords-Supply chain management; flexibility; optimization; uncertainty